Coprocessed excipients with enhanced direct compression functionality for improved tableting performance (2012)
ABSTRACT: It is necessary to have excipients with excellent functional properties to compensate for the poor mechanical properties and low aqueous solubility of the emerging active ingredients. Therefore, around 80% of the current drugs are not suitable for direct compression and more advanced excipients are required. Further, conventional grades of excipients cannot accommodate the technologically advanced high speed rotary tablet presses which require a powder with excellent flow, good compressibility, compactibility, particle size distribution and homogeneity of the ingredients. Co-processed excipients have been created to enhance the functional properties of the excipients and reduce their drawbacks. Co-processing is defined as the combination of two or more excipients by a physical process. Co-processed excipients are adequate for direct compression since they become multifunctional and thus, their dilution potential is high eliminating the need for many excipients in a formulation. In some cases, they are able to hold up to 50% of the drug in a formulation rendering compacts of good tableting properties. This study describes and discusses the functionality enhancement of commercial and investigational excipients through co-processing.